0045 Characterising adoption of precautionary risk management guidance for nanomaterials, an emerging occupational hazard. (23rd June 2014) - Schubauer-Berigan, Mary; Dahm, Matthew; Schulte, Paul; Hodson, Laura; Geraci, Charles
Abstract : Objectives: Exposure to engineered nanomaterials, ENM, (substances with at least one dimension of 1–100 nm) has been of increased interest, with the recent growth in production and use of nanomaterials worldwide. Various organisations have recommended methods to minimise exposure to ENM. The purpose of this study was to evaluate the extent to which U. S. companies follow the guidelines for reducing occupational exposures to ENM, including those issued by the National Institute for Occupational Safety and Health (NIOSH). Method: We collected and reviewed survey data, field reports, and field notes for all NIOSH nanomaterial exposure assessments conducted between 2006 and 2011 to: (1) determine the level of adoption of precautionary guidance on engineering and administrative controls and personal protective equipment (PPE), and (2) evaluate the reliability of companies' self-reported use of engineering and administrative controls and PPE. Results: Use of PPE was reported by 89% of 46 surveyed or visited companies, and 83% reported using engineering controls for at least some processes to protect workers from airborne exposures to nanoscale materials. In on-site evaluations, we observed that more than 90% of the 16 engineered carbonaceous nanomaterial companies that responded to an industrywide survey were using engineering and administrative controls and PPE as reported or more stringently than reported. Conclusions: Since PPE use was slightly more prevalent than engineering and administrative controls, better communication may be necessary to reinforce the importance of the hierarchy of controls. These findings may also be useful in conducting exposure assessment and epidemiologic research among U. S. workers handling nanomaterials.